2016
DOI: 10.4172/2168-9873.1000232
|View full text |Cite
|
Sign up to set email alerts
|

A Full Spectrum Analysis Methodology Applied to an Anisotropic Overhung Rotor

Abstract: This paper demonstrates the methodology and usefulness of full spectrum analysis on theoretical models and experimental measurements. This method establishes another bridge between model and data that is not currently being used to its greatest advantage. Some experimental devices display full spectrum vibration signals but most often half spectrum is reported. Correlating analytical models with experimental data using full spectrum analysis is similarly underutilized.In this paper, 3D full spectrum plots from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They showed that under conditions when rotary inertia is high and the drive motor power is limited, the rotor system may have difficulty in passing through the critical speed, because much of the supplied energy will be transferred to the lateral vibration of the rotor instead of increasing its rotational speed. Wu et al [24] utilized a 4-DOF model for an overhung rotor with anisotropic supports to represent the experimental rig, which they used to validate their inhouse software for data processing and plotting full-spectrum cascade plots against those produced with commercial software. They were able to observe BW orbits that arise when passing through resonance, but did not investigate this phenomenon further as the focus of their work was on validation of their data processing software.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that under conditions when rotary inertia is high and the drive motor power is limited, the rotor system may have difficulty in passing through the critical speed, because much of the supplied energy will be transferred to the lateral vibration of the rotor instead of increasing its rotational speed. Wu et al [24] utilized a 4-DOF model for an overhung rotor with anisotropic supports to represent the experimental rig, which they used to validate their inhouse software for data processing and plotting full-spectrum cascade plots against those produced with commercial software. They were able to observe BW orbits that arise when passing through resonance, but did not investigate this phenomenon further as the focus of their work was on validation of their data processing software.…”
Section: Introductionmentioning
confidence: 99%